Genetic risk for atrial fibrillation could motivate patient adherence to warfarin therapy: a cost effectiveness analysis - Shiffman, Dov (BMC Cardiovasc Disord, 2015)
BACKGROUND: Atrial fibrillation (AF) increases risk of stroke, and although this stroke risk can be ameliorated by warfarin therapy, some patients decline to adhere to warfarin therapy. A prospective clinical study could be conducted to determine whether knowledge of genetic risk for AF could increase adherence to warfarin therapy for patients who initially declined therapy. As a prelude to a potential prospective clinical study, we investigated whether the use of genetic information to increase adherence could be cost effective. METHODS: Markov model assessed costs and utilities of two care strategies for AF patients who declined warfarin therapy. In the usual care strategy patients received aspirin. In the test strategy genetic risk for AF was assessed (genotype of the 4q25 locus) and some patients with a positive genetic test (≥1 risk allele) were assumed to adhere to warfarin therapy. The remaining patients received aspirin. The incremental cost-effectiveness ratio (ICER) was the ratio of the costs differential and the quality adjusted life-years (QALYs) differential for the two strategies. RESULTS: We found that the 4q25 genetic testing strategy, compared with the usual care strategy (aspirin therapy), would be cost-effective (ICER $ 47,148) if 2.1 % or more of the test positive patients were to adhere to warfarin therapy. The test strategy would become a cost saving strategy if 5.3 % or more of the test positive patients were to adhere to warfarin therapy. If 20 % of test positive patients were to adhere to warfarin therapy in a hypothetical cohort of 1000 patients, 7 stroke events would be prevented and 3 extra-cranial major bleeding events would be caused over 5 years, resulting in a cost savings of ~ $250,000 and a net gain of 9 QALYs. DISCUSSION: A clinical study to assess the impact of patient knowledge of genetic risk of AF on adherence to warfarin therapy would be merited because even a modest increase in patient adherence would make a genetic testing strategy cost-effective. CONCLUSION: Providing patients who declined warfarin therapy with information about their genetic risk of AF would be cost effective if this genetic risk information resulted in modest increases in adherence.